2016
DOI: 10.1016/j.biortech.2015.10.087
|View full text |Cite
|
Sign up to set email alerts
|

Acidogenic fermentation of Scenedesmus sp.-AMDD: Comparison of volatile fatty acids yields between mesophilic and thermophilic conditions

Abstract: Access and use of this website and the material on it are subject to the Terms and Conditions set forth at Acidogenic fermentation of Scenedesmus sp.-AMDD: comparison of volatile fatty acids yields between mesophilic and thermophilic conditions Gruhn, Marvin; Frigon, Jean-Claude; Guiot, Serge R.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=fr L'accès à ce site Web et l'utilisation de son contenu sont assujettis aux conditions présentées dans le site LISEZ CES CONDITIONS ATTENTIVEMENT AVANT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Like most microalgae species in the Scenedesmus genus, S-AMDD is non-motile and colonial; typically forming clumps of f our cells or sometimes eight or more under environmentally stressful conditions [27,28]. In recent years, S-AMDD has been the focus of several studies to assess its potential as a feedstock for biofuels and bioremediation [29][30][31][32][33][34][35][36] while the evaluation of its potential suitability as a novel animal feed ingredient has only just begun [37,38]. In an initial study; S-AMDD demonstrated rapid growth rate and biomass productivity during exponential growth phase and the resulting biomass appeared to have good potential for animal nutrition based on its attractive proximate composition, favorable essential amino acid, fatty acid and elemental profiles and lack of contaminating heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…Like most microalgae species in the Scenedesmus genus, S-AMDD is non-motile and colonial; typically forming clumps of f our cells or sometimes eight or more under environmentally stressful conditions [27,28]. In recent years, S-AMDD has been the focus of several studies to assess its potential as a feedstock for biofuels and bioremediation [29][30][31][32][33][34][35][36] while the evaluation of its potential suitability as a novel animal feed ingredient has only just begun [37,38]. In an initial study; S-AMDD demonstrated rapid growth rate and biomass productivity during exponential growth phase and the resulting biomass appeared to have good potential for animal nutrition based on its attractive proximate composition, favorable essential amino acid, fatty acid and elemental profiles and lack of contaminating heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…By the VFA, yields went down by approximately 45 % from the highest value. Compared with other works, the maximum was 208 mg VFA/g TVS production from microalgal biomass using CSTR under mesophilic conditions [19]. Several digestion scenarios obtained VFA yields of 175 -243 mg VFA/g TVS from sewage, adding different concentrations of wollastonite [20].…”
Section: Vfa Concentrations and Yieldsmentioning
confidence: 76%
“…An interesting aspect is the production of propionic and butyric acid that is expected from the fermentation of protein-rich substrates such as microalgae [24], which could obtain a wide range of PHA copolymers. However, the production of VFA through fermentation of microalgal biomass and the consequent conversion to PHAs has received little attention and needs further study [25][26][27].…”
Section: Introductionmentioning
confidence: 99%